Factors that Influence the Effectiveness of Accounting Information Systems: A Case Study of Government Agency in North Nias Regency, Indonesia - Zalukhu, Rika Surianto; Sinurat, Mangasi; Collyn, Daniel; Hutauruk, Rapat Piter Sony; Syahputra, Ari (International Journal of Business, Economics & Financial Studies, 2023)
An Accounting Information System (AIS) is a system that collects, records and processes financial data and non-financial data related to financial transactions to produce information for decision-making. The decision-making process plays an important role in achieving organizational goals. This study aimed to analyze the factors that influence the effectiveness of Accounting Information Systems (AIS) at the government agency in North Nias Regency. The factors tested are user capability, top management support and education and training. The effectiveness of AIS is the study's dependent variable, while user capabilities, top management support and education and training are independent variables. This research was conducted on employees using AIS at the Regional House of Representative Secretariat, Education Office, and Civil Registry Office of North Nias Regency. The research population was 40. The sampling technique used saturation sampling. The type of data used is primary data. Data were obtained by using research questionnaires. Methods of data analysis using multiple linear regression analysis methods. The analysis results show that user capability, top management support, and education and training have a positive and significant effect on the effectiveness of AIS either partially or simultaneously.